Penguatan Pembelajaran Komunikasi Filosofis Agama Kristen di Sekolah Menengah Kejuruan Palangka Raya - Bumen, Eko Julianto Krismanuel R.; Susanto, Adri; Eksely, Sarah Priskila; Handriani, Yuli; Sinaga, Mei Minarti; Lidia, Lidia; Sanasintani, Sanasintani; Munte, Alfonso (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2024)
This research focuses on the communication values that arose during the field experience practice process at State Vocational High School 2 Palangka Raya. These values were generated through mutual interactions between teachers, students, supervisors, and the community, including the church, family, and local residents. The communication process was achieved through module consultations, twelve meetings with students to revisit the topic, a communicative demonstration stage in the classroom, and a Christmas pageant in early December 2023. The purpose of this service is to fulfill academic administrative requirements and explore alternative communication values in multi-party interactions and Christian religious education. The researchers employ the Participatory Action Research (PAR) approach. The benefits of community service include promoting consistent sustainability and communal awareness among students, facilitating the exchange of thoughts and ideas between Pamong teachers-supervising lecturers and PPL students, and fostering a sense of community joy.